2005
DOI: 10.1007/s11092-006-9000-9
|View full text |Cite
|
Sign up to set email alerts
|

How Do Faculty Make Formative Use of Student Evaluation Feedback?: A Multiple Case Study

Abstract: This multiple case study explored faculty formative use of student evaluation feedback. Results were based on interviews of ten education faculty members at a midwestern research university and reviews of relevant documents. It was found that end of semester student evaluation, originally used for summative evaluation, was also used by faculty for teaching improvement purposes. Faculty cared for student evaluation feedback and used discretion in using the feedback to improve their teaching. Faculty also experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 15 publications
3
46
0
1
Order By: Relevance
“…Summative SETs are the most common way universities evaluate the quality of their faculty and have been around for many years in universities worldwide (Becker & Watts, 1999;Davis, 2009;Lill, 1979;Onwuegbuzie, Witcher, Collins, & Filler, 2007;Parayitam, Desai, & Phelps, 2007;Read, Rama, & Raghunandan, 2001;Yao & Grady, 2005). They have become compulsory in Japan (Burden, 2008) and in most universities in North America (Chen & Hoshower, 1998).…”
Section: Student Evaluations Of Teachingmentioning
confidence: 99%
“…Summative SETs are the most common way universities evaluate the quality of their faculty and have been around for many years in universities worldwide (Becker & Watts, 1999;Davis, 2009;Lill, 1979;Onwuegbuzie, Witcher, Collins, & Filler, 2007;Parayitam, Desai, & Phelps, 2007;Read, Rama, & Raghunandan, 2001;Yao & Grady, 2005). They have become compulsory in Japan (Burden, 2008) and in most universities in North America (Chen & Hoshower, 1998).…”
Section: Student Evaluations Of Teachingmentioning
confidence: 99%
“…Students can provide teachers with valuable feedback about their teaching practices. Second, SET is used for summative decisions, and the results of the evaluations are subsequently used in personnel and tenure decisions (Yao and Grady 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This approach of using student ratings to improve their teaching concurs with advice from other teaching literature regarding best uses of evaluations by students. 31,32 Respondents also commonly stated that they valued the input garnered from student ratings. Almost every study participant reported that when reviewing evaluations, they tend to focus on themes and trends that emerge from qualitative data.…”
Section: A J P Ementioning
confidence: 99%